TRANSFORMASI NITROGEN DI LAUT - Hanny Meirinawati (Pusat Penelitian Oseanografi LIPI, 2019)
NITROGEN TRANSFORMATION IN MARINE ENVIRONMENT. Nitrogen transformations are undertaken by marine organisms as part of their metabolisms, either to obtain nitrogen to synthesize structural components or to gain energy for their growth. Nitrogen can stimulate primer productivity in an aquatic ecosystem. Increasing human activities can cause the increase of the number of nitrogen in the ocean. The increased input of nitrogen which is often accompanied by oxygen limitation has a strong negative effect on benthic metabolism and nitrogen mineralization. The ocean’s nitrogen cycle is driven by complex microbial transformations, including nitrogen fixation, assimilation, nitrification, anammox (anaerobic ammonium oxidation) and denitrification.